How well do vital signs identify children with serious infections in paediatric emergency care? - Thompson, M; Coad, N; Harnden, A; Mayon-White, R; Perera, R; Mant, D (2009)
OBJECTIVES: To determine whether vital signs identify children with serious infections, and to compare their diagnostic value with that of the Manchester triage score (MTS) and National Institute for Health and Clinical Excellence (NICE) traffic light system of clinical risk factors. DESIGN: Prospective cohort of children presenting with suspected acute infection. We recorded vital signs, level of consciousness, activity level, respiratory distress, hydration and MTS category. SETTING: Paediatric assessment unit at a teaching hospital in England. PARTICIPANTS: 700 children (median age 3 years), of whom 357 (51.0%) were referred from primary care, 198 (28.3%) self-referrals and 116 (16.6%) emergency ambulance transfers. Just over half (383 or 54.7%) were admitted. MAIN OUTCOME MEASURES: Severity of infection categorised as serious, intermediate, minor or not infection. RESULTS: Children with serious or intermediate infections (n = 313) were significantly more likely than those with minor or no infection (n = 387) to have a temperature >or=39 degrees C, tachycardia, saturations <or=94% (crt)="" capillary="" or="" refill="" time="">2 seconds. Having one or more of temperature >or=39 degrees C, saturations </or=94%>